A falling-head method for measuring intertidal sediment hydraulic conductivity - Li, Hailong (Ground water, 2010)
This paper presents an in situ falling-head method for measuring hydraulic conductivity of beach sediments in tidal environment. A polyvinyl chloride (PVC) standpipe was vertically pushed into the submerged beach sediments so that its lower part was filled by a sediment column. During the experiment, the sediments were submerged by sea water and the standpipe top was higher than the sea level. The pipe was fully filled with sea water at the beginning of the experiment. Then the water level time series inside and outside the standpipe were recorded. Analytical solutions were derived to describe the relation among the sediment's hydraulic conductivity and the water levels inside and outside the standpipe and used to analyze the experiment data obtained from the intertidal zone of Puqian Bay, Haikou, Hainan Province, China. The water levels predicted by the analytical solution agreed very well with all the experiment data. Experiments for horizontal hydraulic conductivity estimation were also conducted using L-shaped standpipe which bends from vertical to horizontal in the beach sediments. The averaged hydraulic conductivity anisotropy ratio at the study area is about 2.9. After each in situ experiment, the sediments in the standpipe were stored in a plastic box and transported to university laboratory to measure the hydraulic conductivity using falling-head method. It is found that the in situ hydraulic conductivity averages one order of magnitude greater than the laboratory one, indicating that the original beach surface sediments were loose due to tidal and wave actions and that the samples were significantly compacted during the transportation to laboratory